On Linear Algebra Education - Sinan AYDIN (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
Linear algebra is a basic course followed in mathematics, science, and engineering university departments.Generally, this course is taken in either the first or second year but there have been difficulties in teachingand learning. This type of active algebra has resulted in an increase in research by mathematics educationresearchers. But there is insufficient information on this subject in Turkish and therefore it has not beengiven any educational status. This paper aims to give a general overview of this subject in teaching andlearning. These education studies can be considered quadruple: a) the history of linear algebra, b) formalismobstacles of linear algebra and cognitive flexibility to improve teaching and learning, c) the relation betweenlinear algebra and geometry, d) using technology in the teaching and learning linear algebra.Mathematicseducation researchers cannot provide an absolute solution to overcome the teaching and learning difficultiesof linear algebra. Epistemological analyses and experimental teaching have shown the learning difficulties.Given these results, further advice and assistance can be offered locally.